The Relationship Between Kiai and Santri from the Perspective of Symbolic Interactionism in Madura - Hanun Asrohah; Ismail Ismail (Jurnal Studi Pendidikan Agama Islam, 2026)
The relationship between kiai and santri at Islamic boarding schools (pesantren) in Madura represents a strategically significant social phenomenon for academic inquiry, given the profound influence of the kiai in shaping the character, values, and identity of santri with broad implications for Madurese social order. Nevertheless, the dynamics of this relationship have not been fully explored through adequate theoretical frameworks, particularly from a symbolic interactionism perspective. This study aims to identify interactional symbols in the kiai-santri relationship, describe the internalization of pesantren values through symbolic media and examine the construction of santri identity as a product of meaning negotiation in interaction with the kiai. This research employs a qualitative approach with an ethnographic design, conducted at three pesantren in Pamekasan and Sumenep Regencies, Madura, through participatory observation, in-depth interviews, and documentary study. The findings reveal three key outcomes: first, kiai charisma is socially constructed through material, linguistic, and ritualistic symbols; second, pesantren values are internalized through symbolic pedagogy encompassing ngaji practice, collective obedience rituals, and body language; and third, santri identity is formed through three phases adoption, negotiation, and consolidation resulting in a hybrid identity. This research contributes to the development of pesantren sociology grounded in Mead and Blumer's symbolic interactionism theory.